THE EFFECT OF WORK ENVIRONMENT, EMPLOYEE ENGAGEMENT, AND EMOTIONAL INTELLIGENCE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Madelin Sarah; Suryani Maryam (SEAN Institute, 2023)
This study aims to investigate the effects of work environment, employee engagement and emotional intelligence on organizational citizenship behaviour (OCB). Data collection techniques through questionnaires were distributed to 76 respondents.The data were gathered by a questionnaire survey, and Partial Least Squares analysis was used as the data analysis approach. The results obtained that work environment has a significant effect on organizational citizenship behavior. Employee engagement has a significant effect on organizational citizenship behavior and emotional intelligence has a significant effect on organizational citizenship behavior. This study contributes to the organisational citizenship behaviour literature by examining how work environmental, employee engagement and emotional intelligence affects organizational citizenship behaviour. The study implies that when organizations are willing to improve the work environment, employee engagement, and emotional intelligence, their employees will be doing more organizational citizenship behavior.